Annual Average Changes in Adult Obesity as a Risk Factor for Papillary Thyroid Cancer: A Large-Scale Case-Control Study. Issue 9 (March 2016) - Hwang, Yunji; Lee, Kyu Eun; Park, Young Joo; Kim, Su-Jin; Kwon, Hyungju; Park, Do Joon; Cho, Belong; Choi, Ho-Chun; Kang, Daehee; Park, Sue K.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: We evaluated the association between weight change in middle-aged adults and papillary thyroid cancer (PTC) based on a large-scale case-control study. Our study included data from 1551 PTC patients (19.3% men and 80.7% women) who underwent thyroidectomy at the 3 general hospitals in Korea and 15, 510 individually matched control subjects. The subjects' weight history, epidemiologic information, and tumor characteristics confirmed after thyroidectomy were analyzed. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were determined for the annual average changes in weight and obesity indicators (body mass index (BMI), body surface area, and body fat percentage (BF%) in subjects since the age of 35 years. Subjects with a total weight gain ≥10 kg after age 35 years were more likely to have PTC (men, OR, 5.39, 95% CI, 3.88–7.49; women, OR, 3.36, 95% CI, 2.87–3.93) compared with subjects with a stable weight (loss or gain <5 kg). A marked increase in BMI since age 35 years (annual average change of BMI ≥0.3 kg/m 2 /yr) was related to an elevated PTC risk, and the association was more pronounced for large-sized PTC risks (<1 cm, OR, 2.34, 95% CI, 1.92–2.85; ≥1 cm, OR, 4.00, 95% CI, 2.91–5.49, P heterogeneity = 0.005) compared with low PTC risks. Weight gain and annual increases in obesity indicators in middle-aged adults may increase the risk of developing PTC.